Holistic Management For Severe Oral Lichen Planus: A Case Report - Nik Mohd Rosdy, Nik Mohd Mazuan; Purwaningsih, Nyi Mas Siti (Journal of Dentistry Indonesia, 2021)
Oral lichen planus (OLP) is an immunologically mediated mucocutaneous disease associated with various factors including systemic diseases, with a higher prevalence in females than males. The majority of OLP cases are accompanied by symptoms of discomfort and/or pain. Treatment of OLP can be challenging due to its unknown aetiology and involvement of multiple contributing factors. Objective: Our aim is to report a long-term follow-up case of oral lichen planus with holistic management approach. This report will provide some options to clinicians who are having difficulties in managing OLP cases especially with the medications. Case Report: This case report discusses a female patient who suffered OLP with no definitive treatment prior to referral to us. A thorough history of her problem including psychosocial factors and dietary pattern were obtained. Clinically, the oral mucosa presented characteristics similar to erosive oral lichen planus. Patient reluctance towards pharmacotherapy due to her comorbidities was a challenged in managing her OLP. Hence, a non-pharmacotherapeutic solution was offered by considering psychology and dietary pattern. Conclusion: A severe oral lichen planus with ulcerative background could be managed holistically and not just through a pharmacotherapeutic approach.